Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.3109/13625187.2012.692411
|View full text |Cite
|
Sign up to set email alerts
|

Combined oral contraceptives’ influence on weight, body composition, height, and bone mineral density in girls younger than 18 years: A systematic review

Abstract: Studies in young users are few. Presently, there are no indications of a negative impact of COCs on weight, body composition or height. Lesser increases in BMD cannot be excluded. As the demand for COCs is increasing among the youngest girls, there is a need for prospective studies addressing this issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Even though weight gain is often attributed as a side effect of contraceptive use [51], there is no scientific evidence to indicate that oral contraceptives induce weight gain [52]. Our observation may be due to contraceptive users adopting “obesity-preventive” lifestyle/dietary habits because of the belief that contraceptive use may result in EBW.…”
Section: Discussionmentioning
confidence: 70%
“…Even though weight gain is often attributed as a side effect of contraceptive use [51], there is no scientific evidence to indicate that oral contraceptives induce weight gain [52]. Our observation may be due to contraceptive users adopting “obesity-preventive” lifestyle/dietary habits because of the belief that contraceptive use may result in EBW.…”
Section: Discussionmentioning
confidence: 70%
“…Similarly, a systematic review covering published studies from 1990 to 2012 on patients younger than 18 years old did not show any correlation between combination contraceptives and weight gain or changes in body composition [133]. Various combinations of oral contraceptives studied in 150 women, both obese and normal weight, were not associated with any significant weight gain, changes in body composition, or increases in BMI over 3-4 months [134].…”
Section: Oral Contraceptivesmentioning
confidence: 96%
“…The limited evidence does not support a causal association between use of CHC and weight gain, and there is no consistent evidence that different CHC formulations affect weight differently. A systematic review175 which identified data for women aged under 18 years from nine observational trials, concluded that there is no evidence of an association between CHC use and weight gain in this group of women.…”
Section: Side Effects Associated With Chc Usementioning
confidence: 99%